Gene regulation and the Fis nucleoid-associated protein in Salmonella enterica serovar Typhimurium - Kelly, Arlene (Trinity College (Dublin, Ireland). Department of Microbiology, 2005)
The Fis protein was found to influence the superhelical density of DNA and its ability to do this differed between Salmonella enterica serovar Typhimurium (S. typhimurium) and Escherichia coli (E. coli). Induction of the Fis protein to high levels in S. typhimurium resulted in the concomitant relaxation of the DNA in good correlation with Fis as a transcriptional repressor of the gyrgenes that encode DNA gyrase.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin